(untitled) (Fiep Bulletin - online, 2014)
The dichotomy between body and mind was already perceived from ancient Greece in the sixth century a.C. With the advent of philosophy, however, this was taken to the extreme in the seventeenth century by René Descartes. The method Cartesian generated a fragmentation in scientific knowledge. As Education is directly linked to science, this way of thinking came to dominate the formal education. Thus the body is now despised in classrooms, where only the intellect is developed. Even the discipline Physical Education who works directly with the body ends up expanding it, but with a reverse process, denying the intellect. Among the possibilities to overcome this dichotomy, the Science of Human Motricity is in the field of Physical Education, a way to consider the student as a whole, where the corporeity is expressed through gesture motor intentional. This intent is demonstrated by the gesture human being contextualized in the culture in which it lives. Thus, denying the culture of the student, is not to educate the autonomy or the critical sense, but for the conformism and acceptance. An education concerned with the formation of critical and creative people to be in and the culture, in which the body of the student has space in classrooms and the intelligibility also win your space in class for Physical Education. It is the objective of this article, pointing the oppression that the 286 body is suffering the mind-body dichotomy and the possibilities of overcoming the educational system and more specifically in the discipline Physical Education.